Determination of n-acetyl β-d glucosaminidase enzyme activity in bovine milk for the early diagnosis of subclinical mastitis - Mehmet Nizamlıoğlu; Leyla Kalaycıoğlu; Dursun Ali Dinç; Osman Erganiş; Firuze Özeren (Eurasian Journal of Veterinary Sciences)
In this present study, N-acetyl-B-D-glucosaminidase (NAG ase) activity and microbiological investigations were carried out in milk samples for the early diagnosis of subclinical mastitis in dairy cows. Forty Holstein cow, in 4-5 years old were used as materials. NAG ase activity, PMN and microbiologic values, in milk samples in which CMT test performed, were compared. NAG ase activity was found 33.08±4.62 U/L and 90.70±11.98 in healty and mastitic milk sampes respectively and differences were found statistically significant (P<0.05). The PMN values were determined average 282655±57035 in healty milk and 1236396±216308 in mastitic milk samples. Staphylococcus, Klebsiella pneumonia, Corynebacterium ssp agents were identified in milk samples. As a result, it was useful to determine NAG ase activity, PMN and CMT test in milk samples for the early diagnosis of subclinical mastitis.